Juridical Analysis of Entry and Exit Points for Animal and Plant Quarantine Carrier Media - Ferry Hamdhani; Fadlan Fadlan; Christiani Prasetiasari; Erniyanti Erniyanti (Jurnal Ilmiah Pertanian dan Peternakan, 2025)
Purpose: The purpose of this study was to determine the legal arrangements for the place of entry and release of animal and plant quarantine carrier media, and the factors, constraints, solutions, and implementation of the place of entry and release of animal and plant quarantine carrier media. Methodology: The research method of this thesis is normative juridical (legal research) through a literature study with an empirical juridical approach (sociological juridical) through field studies aimed at empirically obtaining legal knowledge. Results: Quarantine entry and exit regulations are based on Articles 86 and 87 of Law No. 21 of 2019. The Batam Quarantine Center shows strong biosecurity efforts despite challenges in resources and coordination. Solutions include technology use, staff training, and improved collaboration. Conclusions: The enforcement of quarantine entry and exit points in Batam reflects Indonesia’s strong commitment to biological security. Despite logistical and human resource challenges, legal compliance is improved through regulatory reforms, stakeholder collaboration, and continuous system evaluations. These measures collectively strengthen the country’s quarantine system and environmental protection. Limitation: This study is geographically limited to Batam City and relies primarily on qualitative analysis, which may not reflect broader implementation challenges across other regions in Indonesia. Contribution: This study contributes to the development of quarantine law enforcement strategies and provides practical insights for policymakers and quarantine agencies to strengthen institutional coordination, improve resource allocation, and enhance the effectiveness of biosecurity at entry-exit points.